Measuring the impact of principals' competence and facilities on teachers' achievement in Public Vocational High Schools in Palembang City: A multivariate analysis - Yuniarti, Yuniarti; Walajro, Jumadi (Utan Kayu Publishing, 2024)
The level of teacher performance in carrying out their main duties at school is greatly influenced by the competence of the school principal and the completeness of school facilities. This study examines the influence of school principals' competence and the completeness of school facilities on the performance of vocational high school (SMK) teachers in Palembang City. Employing a quantitative correlational design, the study involved 55 teachers from three vocational high schools.. The research instrument was validated using Pearson Product Moment, and data reliability was verified using the Cronbach Alpha test. The research results reveal that (1) the principal's competence is related to teacher performance, and the principal's competence has minimal influence on the performance of vocational school teachers. (2) Facilities and infrastructure were found to be related to vocational school teacher performance. Facilities and infrastructure have a significant effect on the performance of vocational school teachers. (3) The competence of the school principal, facilities and infrastructure have a significant influence on the performance of vocational school teachers. These findings underscore the importance of developing school leadership and enhancing facilities to support teacher performance. The study invites further research to explore additional factors affecting teacher performance and strategic implementation to improve the quality of vocational education. Implications for educational practice include the enhancement of leadership training programs and investment in adequate educational infrastructure.